PEMANFAATAN KARBON AKTIF LIMBAH KELAPA SAWIT SEBAGAI MEDIA ALTERNATIF FILTER GAS H2S PADA BIOGAS - Hegar Partogy Ambarita (Machine : Jurnal Teknik Mesin, 2020)
ABSTRACT This study aims to purify biogas from impurities gas, namely H2S (hydrogen sulfide) which, if it has a high content or is not removed can cause poisoning, reduce the combustion process and can damage the machining components so that it becomes corrosive. Several studies with various purification technologies have been developed, namely the method of absorbs by using various types of absorbent. One of the absorbents used is activated carbon derived from palm oil waste, which are oil palm shells and fibers with a composition of 75% and 25% that undergo combustion processes in a boiler furnace to a temperature of 1400⁰C, the result of this combustion will produce activated carbon to be used as absorbent gas biogas impurities. This research was conducted using furification filters or can be called dry filters. This method is considered very effective for absorbing H2S gas content in biogas. To determine the effectiveness of absorption, then the addition of activated carbon to the dry filter is carried out. The experiment was carried out by spraying H2S gas through a filter media that had been made. The experimental results show the use of activated carbon in the dry filter can reduce H2S levels by 90%.